THE EFFECT OF ONE STAY THREE STRAY METHOD ON THE ABILITY OF THE SECOND YEAR STUDENTS OF SMPN 1 PANGKALAN KURAS IN COMPREHENDING RECOUNT TEXT - Nadya Putri Anggina; Rumiri Aruan; M Syarfi (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: This research is aimed to find out if there is a significant effect of One Stay Three Stray method on the ability of the second year students of SMPN 1 Pangkalan Kuras in comprehending recount text. The research design was a pre-experimental research with one group pre-test and post-test design. The sample was selected by cluster random sampling. The mean score of post-test (76.30) was higher than mean score of the pre-test (53.50).Therefore, alternative hypothesis was accepted and null hypothesis was rejected. It means that there is a significant effect of One Stay Three Stray method on the ability of the second year students of SMPN 1 Pangkalan Kuras in comprehending recount text.Key Words: Reading,Reading Comprehension,One Stay Three Stray,Recount Texts